An Analysis of Service Quality and Price on Customer Satisfaction at Madani Hotel Medan - Ridayat Adi Amri; Nurafrina Siregar; Ocdy Amelia (Jurnal Multidisiplin Sahombu, 2025)
This study aims to analyze the influence of service quality and price on customer satisfaction at Madani Hotel Medan. Service quality and pricing are considered crucial factors that affect customer perceptions and loyalty in the hospitality industry. The research uses a quantitative approach with a survey method, distributing questionnaires to hotel guests as respondents. Data were analyzed using multiple linear regression to determine the partial and simultaneous effects of the independent variables. The results show that both service quality and price have a significant and positive influence on customer satisfaction. Among these, service quality is the more dominant factor affecting guest satisfaction. The findings suggest that improving service consistency and offering competitive pricing are key strategies for enhancing customer experience and sustaining customer loyalty at Madani Hotel Medan.